Trace fossils, sedimentary facies and parasequence architecture from the Lower Cretaceous Mulichinco Formation of Argentina: The role of fair-weather waves in shoreface deposits - Wesolowski, Lindsey J. N. (2018)
Fil: Wesolowski, Lindsey J. N. University of Saskatchewan. Department of Geological Sciences. Saskatoon, Canada.